2005
DOI: 10.1111/j.0020-8833.2005.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

"Women, Children and Other Vulnerable Groups": Gender, Strategic Frames and the Protection of Civilians as a Transnational Issue

Abstract: This article offers an explanation for the use of gender essentialisms in transnational efforts to advocate for the protection of war‐affected civilians. I question why human rights advocates would rely upon such essentialisms, since they arguably undermine the moral logic of the civilian immunity norm on which their normative claims are based. This can be understood, I argue, as part of a strategic framing process in which pre‐existing cultural ideas, filtered through an environment characterized by various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 57 publications
1
111
0
2
Order By: Relevance
“…This overemphasis on women and children as the victims of conflict has two problematic consequences. First, the focus of this narrative on women and children has disempowered these groups and diminished their potential to be seen as autonomous political actors; this is especially true for adult women (Alison 2007;Carpenter 2005). This viewpoint supports the arguments outlined above in that it can make applications from women based on political persecution in civil conflict less compelling.…”
Section: Women and Gender-based Discriminationmentioning
confidence: 83%
See 2 more Smart Citations
“…This overemphasis on women and children as the victims of conflict has two problematic consequences. First, the focus of this narrative on women and children has disempowered these groups and diminished their potential to be seen as autonomous political actors; this is especially true for adult women (Alison 2007;Carpenter 2005). This viewpoint supports the arguments outlined above in that it can make applications from women based on political persecution in civil conflict less compelling.…”
Section: Women and Gender-based Discriminationmentioning
confidence: 83%
“…However, there are other issues to consider. First, there is a strong victimization narrative in the civil war literature that has traditionally viewed women and children as the primary victims in times of conflict (Alison 2007;Bhabha 2004a;Carpenter 2005). This overemphasis on women and children as the victims of conflict has two problematic consequences.…”
Section: Women and Gender-based Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…An experiencebased, testimony-centered approach to seeing how people live war and security might be a way forward to separate thinking about and making war from its (current) inherent sexisms and cissexisms. Carpenter (2005) found that civilian aid organizations identify those who are civilians by female sex and motherhood. Sjoberg and Gentry (2007) noted that, often, potential terrorists are identified by their male sex.…”
Section: Resultsmentioning
confidence: 99%
“…and with how they promote normative change (Acharya, 2004;Carpenter, 2005).17 However, norm formation and diffusion in international politics also involves other types o f norms. These authors usually ignore the essential quality and special appeal o f some o f these international norms that are identified as responding to existential threats to peace and security.18 15 The idea o f IOs working as "teachers o f norms" is from Finnemore (1993).…”
Section: Theoretical Perspectives On Norm Formation and The Securitismentioning
confidence: 99%